An integrated review: connecting Covid-era hospital visiting policies to family engagement - Morgan, Jennifer D.; Gazarian, Priscilla; Hayman, Laura L. (Frontiers in Public Health, 2023)
Introduction Family engagement and patient-family-centered care are vitally important to improve outcomes for patients, families, providers, hospitals, and communities. Both constructs prioritize providers forming partnerships with patients and their families. The domains of family-engaged care include presence, communication, shared-decision making, family needs, contribution to care, and collaboration at the institutional level. This integrative review describes the extent to which the domains of family engagement are present in the literature about Covid-era hospital visiting policies. Methods A search of four databases resulted in 127 articles and one added through data mining. After review, 28 articles were synthesized and analyzed into an integrative review of family engagement in the hospital with Covid-era visiting policies as the backdrop. Results The 28-article review resulted in an international, multidisciplinary perspective of diverse study designs. The review’s sample population includes 6,984 patients, 1,126 family members, 1,174 providers, 96 hospitals, 50 health centers, 1 unit, and 257 documents. While all the domains are represented, presence is the prevailing domain, identified in 25 out of the 28 (89%). Discussion Presence is recognized as facilitating the other domains. Because the concept of collaboration is largely absent in the literature, it may provide healthcare institutions with a growth opportunity to facilitate and promote family engagement. This review is the first step in operationalizing family engagement in the hospital setting, especially when presence is challenging.